Evaluation of the association between tuftelin gene polymorphism, Streptococcus mutans, and dental caries susceptibility - Priti Sushil Jain; Satyawan G Damle; Shely P Dedhia; Abdulkadeer M Jetpurwala; Tejashri S Gupte (Wolters Kluwer Medknow Publications, 2020)
Context: Dental caries can be conceptualized as an interaction between genetic and environmental factors. Aims: The purpose of this study was to identify any polymorphism in tuftelin gene and its association with dental caries susceptibility, either singly or in combination with the microbial causing agent: Streptococcus mutans. Settings and Design: The presented study included a total of 30 children of age group 12-16 years categorized into two groups: 15 children with no detectable caries in Group I and 15 children with high caries (DMFS ≥10) in group II. Materials and Methods: The stimulated salivary samples were inoculated in mitis salivarius bacitracin agar plates and growth of S. mutans was estimated. DNA extraction was done from whole blood and amplification was done with the help of real-time polymerase chain reaction technique. Oligonucleotide primers were designed to flank single nucleotide polymorphism in the gene. Statistical Analysis Used: The collected data was statistically analyzed by unpaired t-test, paired t-test, Chi-square test, Pearson correlation, and regression analysis. Results: The difference in mean salivary S. mutans counts between the two groups was highly significant. Correlation between tuftelin gene polymorphism and dental caries susceptibility was not significant in both Group I and Group II. Only 4.1% of the variability in dental caries risk can be explained by interaction between tuftelin gene and S. mutans. Conclusions: Future research studies including parents and siblings should be carried out to focus on further investigation into the mechanism of this gene-environment interaction.